Frequently Asked Questions about Soil Moisture Sensor Irrigation Controllers (SMS) - Paul Monaghan; Ondine Wells; Michael Dukes; Maria Morera; Laura A. Warner (EDIS)
A soil moisture sensor (SMS) is a device that detects how much moisture is in the soil and prevents an irrigation system from running when it is not needed. This 4-page fact sheet explains how the technology functions as well as how to install, program, operate, and maintain an SMS for a money- and water-wise sustainable home landscape that’s lush and beautiful. Written by Paul Monaghan, Ondine Wells, Michael Dukes, Maria Morera, and Laura Warner, and published by the Department of Agricultural Education and Communications, September 2015.